Effect of packaged coffee drinks consumption to corrosion rate of stainless steel orthodontic wire - Mansjur Nasir; Defrina Y. Zulfajri; Karima Q. Mansjur (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effect of packaged coffee drinks consumption to corrosion rate of stainless steel orthodontic wire.Material and Methods: This study is laboratory experimental with post-test only with control group design and using stainless steel orthodontic wire with total of 16 samples. The wire length is 6 cm and diameter is 0.41 mm. Samples were divided into 4 groups with 1 group of artificial saliva and 3 groups with a packaged coffee drinks substitution. Measurement of corrosion rate was done by using potensiostat tool and data analysis using SPSS version 23 and Kruskal Wallis and post hoc Mann Whitney test with significant value of p>0.05.Results: Luwak and robusta packaged coffee group had lower corrosion rate value than the control group. While arabica packaged coffee group had higher corrosion rate value than the control group.Conclusion: Arabica packaged coffee drinks had the biggest effect on corrosion rate of stainless steel orthodontic wire.